2015
DOI: 10.3892/or.2015.4352
|View full text |Cite
|
Sign up to set email alerts
|

Paxillin is positively correlated with the clinicopathological factors of colorectal cancer, and knockdown of Paxillin improves sensitivity to cetuximab in colorectal cancer cells

Abstract: Abstract. Paxillin (PXN) encodes a 68-kDa focal adhesionassociated protein and plays an important role in signal transduction, regulation of cell morphology, migration, proliferation and apoptosis. The aim of the present study was to evaluate the relationship between PXN and clinicopathological factors in colorectal cancer, the role of PXN in cetuximab resistance, and whether knockdown of PXN expression could improve the sensitivity to cetuximab in colorectal cancer cells. In the present study, immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“… 37 Previous studies have shown that Paxillin expression was associated with lymph node metastasis in lung and colon cancer. 11 , 38 In this study, we demonstrated that Paxillin expression and other clinicopathological factors, such as raised PSA level, Gleason score, tumor grade, positive surgery margin, extracapsular extension and seminal vesicle invasion, were associated with PCa metastasis to the pelvic lymph nodes. Thus, we speculate that PCa metastasis is a multi-factoral-induced phenomenon, and further studies are needed to elucidate the underlying molecular mechanisms that can be targeted to effectively control disease progression and provide a means to evaluate and predict PCa metastasis.…”
Section: Discussionmentioning
confidence: 67%
“… 37 Previous studies have shown that Paxillin expression was associated with lymph node metastasis in lung and colon cancer. 11 , 38 In this study, we demonstrated that Paxillin expression and other clinicopathological factors, such as raised PSA level, Gleason score, tumor grade, positive surgery margin, extracapsular extension and seminal vesicle invasion, were associated with PCa metastasis to the pelvic lymph nodes. Thus, we speculate that PCa metastasis is a multi-factoral-induced phenomenon, and further studies are needed to elucidate the underlying molecular mechanisms that can be targeted to effectively control disease progression and provide a means to evaluate and predict PCa metastasis.…”
Section: Discussionmentioning
confidence: 67%
“…Changes in expression or localisation of paxillin and FAK are frequently associated with changes in the metastatic potential of cancer cells and previous work in our laboratories has demonstrated such changes to paxillin and FAK following alterations in cellular motility and adhesion in response to the targeting or overexpression of a variety of molecules in breast and prostate cancer models (17,43,44). Additionally, changes in paxillin expression or phosphorylation have also been implicated in resistance to therapies such as cisplatin and cetuximab in non-small cell lung cancer and colorectal cancer (19,20).…”
Section: Discussionmentioning
confidence: 93%
“…Another study in breast cancer has suggested that paxillin levels correlate with ERBB2 receptor tyrosine kinase 2 (HER2) amplification and may also influence responsiveness of tumours to chemotherapy, although this appeared to depend on the HER2 status of the tumours (16). Changes in paxillin and FAK expression, phosphorylation or localisation are often associated with enhanced migratory potential and may also represent a means of resistance to cancer therapies (17)(18)(19)(20).…”
Section: In the Mda-mb-231 Breast Cancer Knockdown Model Cells Had Lmentioning
confidence: 99%
“…Results from our clinical cohort suggest that ovarian cancer is similar to other solid tumours, including breast and lung, in which increased transcript copy numbers of FAK and paxillin are linked to poor prognosis [23][24][25][26][27][28]. Our clinical cohort isolated those groups of patients who had poorly differentiated tumours, and those patients who died from the disease and/or had associated incidence.…”
Section: Discussionmentioning
confidence: 98%